Interaksi Sosial Transmigran dengan Komunitas Lokal di Desa Ketong, Kecamatan Balaesang Tanjung, Kabupaten Donggala - Ika Listiqowati; Ihwatun Hasanah; Kaharuddin Nawing; Amalia Novarita (Jurnal Sosiologi Andalas, 2021)
This paper aims to (1) Describe the form of cooperation between transmigrants and local communities in Ketong Village; (2) Describe the form of accommodation between transmigrants and local communities in Ketong Village, and; (3) Describe the form of assimilation between transmigrants and local communities in Ketong Village. This research is descriptive and qualitative. Data collection techniques consisted of observation, interviews, documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the writing are (1) The form of cooperation between transmigrants and local communities in Ketong Village is spontaneous cooperation, namely helping each other when grieving, direct cooperation, namely cooperation when there is an instruction from the village head, and traditional cooperation, namely cooperation when welcoming guests, cooperation during celebrations, and kumpulan / cooperation in the agricultural sector. (2) The form of accommodation between transmigrants and local communities in Ketong Village is tolerance, namely, respect for cultural differences, and visiting each other during holidays. (3) The form of assimilation between transmigrants and local communities in Ketong Village is assimilation in the field of agricultural crops and marriage